PERAN KUALITAS KEHIDUPAN KERJA DAN KEPUASAN KERJA SEBAGAI MEDIASI ANTARA KEPEMIMPINAN SPIRITUAL TERHADAP KINERJA PEGAWAI: BUDAYA ORGANISASI SEBAGAI PEMODERASI (STUDI KASUS PADA PEGAWAI RUMAH SAKIT GIGI DAN MULUT PENDIDIKAN BAITURRAHMAH) - Rizki, Fardiansyah Muhammad; Zaitul, Zaitul; Harahap, Erni Febrina (Ensiklopedia of Journal, 2024)
The theoretical implications of research on the role of quality of work life and job satisfaction as mediation between spiritual leadership and employee performance, with organizational culture as a moderator, are as follows: Spiritual Leadership as a Foundation: This research confirms that spiritual leadership can be a strong foundation in improve the quality of work life and employee job satisfaction. According to spiritual leadership theory, leaders who apply spiritual values in their leadership can create a harmonious and motivational work environment. This theory shows that spiritual leadership not only focuses on achieving organizational goals, but also on the welfare and holistic development of employees, thereby motivating them to provide maximum contribution. Mediation Through Quality of Work Life and Job Satisfaction: The findings of this study indicate that quality of work life and job satisfaction play an important role as mediators between spiritual leadership and employee performance. Based on mediation theory, these variables explain how or why spiritual leadership affects employee performance. Employees who experience spiritual leadership tend to have a better quality of work life and higher job satisfaction, which in turn improves their performance. This theory emphasizes the importance of positive working conditions and job satisfaction as factors that bridge the influence of spiritual leadership on employee performance. Organizational Culture as a Moderator: The main implication is the role of organizational culture as a moderator in the relationship between quality of work life, job satisfaction and employee performance. Moderating theory explains that organizational culture can strengthen or weaken the relationship between these variables. A positive, inclusive and supportive organizational culture can strengthen the positive influence of quality of work life and job satisfaction on employee performance. On the other hand, a non-conducive organizational culture can hinder the positive effects of mediation. This confirms the importance of considering organizational culture in the development of leadership and human resource management strategies. Thus, this research provides a deeper understanding of how the interaction between these variables contributes to employee performance in the context of spiritual leadership and organizational culture. This can help organizations develop more effective leadership and culture strategies to improve the quality of work life, job satisfaction, and ultimately overall employee performance.Keywords: Mediation, Quality of Work Life, Job Satisfaction, Employee Performance